Hospitalisation for rotavirus gastroenteritis in the paediatric population in the Veneto Region, Italy - Saia, Mario (BioMed Central, 2010)
BACKGROUND: This study evaluates the epidemiological impact of RVGE hospitalisation in the Veneto Region during the period spanning from 2000-2007 along with the associated costs. The analysis was conducted in an area where rotavirus vaccination is not included into immunization programmes and is an attempt to assess the potential benefits of such introduction. METHODS: To update the estimates of acute RVGE hospitalisation rates in children ≤5 years in the Veneto Region, we conducted an 8 year retrospective observational population-based analysis (2000-2007). RESULTS: Over the study period, a total of 4,119 admissions for RVGE were reported, with a mean hospital stay of 3.5 days. The population-based hospitalisation RVGE incidence rate was 195.8 per 100,000 children aged ≤5 years (lower than other European countries). CONCLUSIONS: RVGE is an important cause of paediatric hospitalisation in the Veneto Region. The data reaffirm the substantial burden of rotavirus hospitalisations in children and the potential health benefits of the vaccination as well as the possibility of adding rotavirus vaccination to the current schedule.